Resilience through placemaking: Public spaces in Rotterdam's climate adaptation approach. - Peinhardt, Katherine (My University, 2021)
Urban public spaces are an opportunity for comprehensive climate adaptation and improved resilience. As a key part of a city's physical infrastructure, it has long been clear that public spaces can be physically reinforced to absorb or weather the shocks of the climate crisis. As a result, many public spaces are designed to materially resist local impacts of the climate crisis, but fewer have seen efforts to harness their potential for improving social resilience. It is increasingly clear that the unique role of public spaces in civic life positions them to enhance not only physical resilience, but also to support the types of interpersonal connections essential to addressing shared challenges like the climate crisis. Through a "placemaking" approach, both of these goals can be layered into a single space: meaning that public spaces not only protect people from climate hazards, but also provide socially vibrant places and contribute to social cohesion. As climate-adaptation plans become more widespread in cities across the globe, innovators such as the City of Rotterdam are leading the way by incorporating public spaces into their strategy. The most prominent example of this change is Waterplein Benthemplein, an early example of a "water square", which absorbs excess stormwater while providing public space. This paper, based on a paradigmatic case study, examines the policy context for Rotterdam with regard to public spaces, climate adaptation, and long-standing practices around water management. It continues with an observational analysis of Waterplein Benthemplein, which provides best practices of, and potential pitfalls for, public space projects aimed at adaptation and/or resilience building.
Keywords: Kommunaler Klimaschutz; Klimaanpassung; Städtebauliche Maßnahme; Öffentlicher Raum; Freiraumgestaltung; Mehrfachnutzung; Wassermanagement; Hochwasserschutz; Regenrückhaltebecken; Stadtplatz